Experimental evaluation on elevated temperature fatigue and tensile properties of one selective laser melted nickel based superalloy. (April 2019) - Jiao, Z.H.; Lei, L.M.; Yu, H.C.; Xu, F.; Xu, R.D.; Wu, X.R.
Highlights: SLM fabricated nickel based superally K536 is studied, which is scarce in present reports. Tensile performance at room and elevated temperatures (400–700 °C) of SLM K536 and its wrought counterparts are compared and analyzed. The anisotropy of tensile and fatigue performances at room and elevated temperatures are investigated. The surface slippage and the internal facet are the main characteristics of crack initiation at elevated temperatures to SLM K536 specimens. Abstract: Additive manufacturing techniques show more and more utilization potentialities in today's aviation industry. In order to ensure safe operation of additive manufactured parts, it is important to have their mechanical properties well-characterized and assessed. In this study, elevated temperature tensile and fatigue performances of one selective laser melting (SLM) fabricated nickel based superalloy named K536 are investigated. A series of tensile tests at room and 400–700 °C temperature range and stress-controlled fatigue tests at 400 °C and 600 °C are employed. Effects of building orientation and temperature on tensile and fatigue properties are analysed. Scanning electron microscopy is used to examine the fracture surfaces of fatigue specimens to qualify the failure mechanism and crack initiation sites. The SLM K536 exhibits higher tensile strength in contrast with the wrought alloy at different tested temperatures. It is found that the anisotropy of monotonic tensile and fatigue properties is not significant. The scatter of fatigue data in the near-fatigue limit region shows more serious at 400 °C than 600 °C, indicating that a more conservative life prediction method will be suitable to ensure safety at lower temperature. The surface slippage and the internal facet are the main characteristics of crack initiation at elevated temperatures to SLM K536 specimens with shorter fatigue life and longer fatigue life, respectively.